2003
DOI: 10.1037/0278-7393.29.6.1160
|View full text |Cite
|
Sign up to set email alerts
|

Prototype and Exemplar Accounts of Category Learning and Attentional Allocation: A Reassessment.

Abstract: In a recent article, J. P. Minda and J. D. Smith (2002) argued that an exemplar model provided worse quantitative fits than an alternative prototype model to individual subject data from the classic D. L. Medin and M. M. Schaffer (1978) 5/4 categorization paradigm. In addition, they argued that the exemplar model achieved its fits by making untenable assumptions regarding how observers distribute their attention. In this article, we demonstrate that when the models are equated in terms of their response-rule f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 38 publications
(202 reference statements)
4
83
0
Order By: Relevance
“…Cognitive psychologists have extensively studied the ways in which people group objects into categories, investigating issues such as whether people represent categories in terms of exemplars or prototypes (J. D. Smith & Minda, 1998;Nosofsky & Zaki, 2002;Minda & Smith, 2002;Storms et al, 2000;Nosofsky, 1988;Nosofsky & Johansen, 2000;Zaki et al, 2003;E. E. Smith et al, 1998;Heit & Barsalou, 1996).…”
Section: Methods For Studying Categoriesmentioning
confidence: 99%
“…Cognitive psychologists have extensively studied the ways in which people group objects into categories, investigating issues such as whether people represent categories in terms of exemplars or prototypes (J. D. Smith & Minda, 1998;Nosofsky & Zaki, 2002;Minda & Smith, 2002;Storms et al, 2000;Nosofsky, 1988;Nosofsky & Johansen, 2000;Zaki et al, 2003;E. E. Smith et al, 1998;Heit & Barsalou, 1996).…”
Section: Methods For Studying Categoriesmentioning
confidence: 99%
“…Multiple systems arguments have also been made in such diverse fields as reasoning (Sloman, 1996), motor learning (Willingham, 1998), discrimination learning (Kendler & Kendler, 1962), function learning (Hayes & Broadbent, 1988), and identification (Ashby, Waldron, Lee, & Berkman, 2001), as well as by other category learning researchers (e.g., Brooks, 1978;Erickson & Kruschke, 1998;Nosofsky, Palmeri, & McKinley, 1994). Nevertheless, many recent categorization articles have argued for a single system that mediates all category learning (Nosofsky & Kruschke, 2002;Pothos, 2005;Zaki, Nosofsky, Jessup, & Unversagt, 2003;Zaki, Nosofsky, Stanton, & Cohen, 2003). Although we cannot rule out the possibility that some single system model could account for the present results, a significant challenge for single system theorists is to account for the growing number of observed dissociations between rule-based and information-integration tasks within the same unified model.…”
Section: Discussionmentioning
confidence: 99%
“…If GCMg mimics PRT, then GCMg should not only fit its own data better than PRT would, but it should also fit data generated by PRT better than PRT itself does. Nosofsky and Zaki (2002;Zaki et al, 2003) showed that this was not always the case, demonstrating that there are conditions in which GCMg does not mimic PRT.…”
Section: Measuring Model Complexity and Discriminabilitymentioning
confidence: 99%
“…Nosofsky and colleagues (Nosofsky & Zaki, 2002;Zaki, Nosofsky, Stanton, & Cohen, 2003) defended the introduction of the response-scaling parameter, arguing that, among other things, it was necessary to capture the deterministic behavior that participants exhibit early in learning, when they tend to focus on a single dimension of a stimulus. Probably most convincing in countering the claims of Smith and Minda (1998) are the results of two simulations that showed that data generated by PRT were fitted better by PRT than by GCMg.…”
mentioning
confidence: 99%